Implementation of Association Rule With Algorithm Apriori On Loan Data Library and Archives Service Book Regency Sukoharjo - Sari, Septiana Cahaya; Arif Himawan; Murdiyanto, Aris Wahyu (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2025)
The library has an important role in improving literacy, education, and facilitating access to information for the community. The Department of Libraries and Archives of Sukoharjo Regency has a high number of collections and visitors every year. An analysis of book borrowing transaction data is necessary to obtain information that can enhance the quality of services in the Sukoharjo Regency Library. This research aims to process book borrowing data at the Sukoharjo District Library and Archives Office by applying the Knowledge Discovery in Databases method. In addition, this also seeks to implement the Apriori algorithm to discover association rules that illustrate the relationships between books that are often borrowed together by library members, as well as to provide recommendations for book management to the library staff. The Knowledge Discovery in Databases method is used because it is a systematic approach that focuses on collecting hidden knowledge from large and complex data. This method consists of five main stages, namely selection, preprocessing, transformation, data mining, and evaluation. This research succeeded in identifying patterns of book borrowing at the Sukoharjo Regency Library and Archives Service based on 1,052 lending transaction data, with a minimum support of 0.005 and a confidence of 0.2 obtained from 64 association rules.